Demographic Profile and Extra Intestinal Manifestations of Ulcerative Colitis in Nepalese population: Study from TUTH a Tertiary Care Centre, Kathmandu, Nepal - Harsh, Shaneel; Adhikari, Ananya; Parazuli, Parmatma; Pathak, Rahul; Khadga, Prem K; Sharma, Sashi (Journal of Advances in Internal Medicine, 2015)
Background and Aims: This study aims at determining the demographic profile and extra-intestinal manifestations of Ulcerative Colitis in the Nepalese patients treated in a tertiary referral centre. Methods: The study was conducted between February 1, 2014 and January 31, 2015 at the Department of Gastroenterology Tribhuvan University Teaching Hospital, Kathmandu, Nepal. The clinical and epidemiologic data from patients diagnosed to have Ulcerative Colitis were obtained and analysed. Results: During the study period, 60 patients were identified as having ulcerative colitis. Mean age at diagnosis was 34.6 years. The mean duration of illness at diagnosis was 3.7 years. Extra-intestinal manifestations (EIM) were seen in 16.6% of the patients. Sacroilitis was the most common EIM seen in11.6% followed by peripheral arthritis in 6.6% of the patients. Episcleritis, Primary Sclerosing Cholangitis and Erythema Nodosum were seen only in 1.6% each. At the time of presentation, 38.3% (n=23) had proctosigmoiditis , 50% (n=30) left sided colitis and pancolitis was seen in 11.7% (n=7).53.3% patients had mild disease, 38.3% and 8.3 % presented with moderate to severe disease respectively. Conclusion: Peak age of onset for UC in the study was third and fourth decade which was similar to the various studies from Asia and West. Musculoskeletal manifestation was the most common extra- intestinal manifestation of UC in Nepalese population. As Nepal is perhaps the most diverse country in terms of ethnicity, cultural variation, socio-economic status and health care facilities, a comprehensive nationwide data bank involving ethnicity and geographical variation is needed for a better definition of the disease characteristics. Journal of Advances in Internal Medicine 2015;04(01):1-5.